Audio Visual Media as An Effective Solution for Motor Learning - Sumarsono, Adi; Anisa, Anisa (Universitas Pendidikan Indonesia, 2019)
This study was aimed at determining the effectiveness of motion techniques learning using audio visual media. This research was an experimental research. The population of this study was grade VIII students. The sampling process used purposive sampling technique. The samples consisted of 32 students of grade VIII. The instruments used were FCE sheets, observation sheets, assessment of student motor ability, and motor educability tests. The results of the research concluded that audio visual media is an effective solution for learning and teaching motor ability. The visual experience and short term memory storage can be used in correcting movement due to the influence of visualization received by the sense of sight and the sense of hearing. The results of this study can be used as references in teaching motor ability. Moreover, audio visual media can be used for learning a movement skill that requires a complex movement combination. AbstrakPenelitian ini bertujuan untuk mengetahui efektifitas pembelajaran gerak dengan menggunakan media audio visual. Penelitian ini merupakan penelitian eksperimen. Populasi penelitian ini seluruh siswa kelas VIII. Pengambilan sampel menggunakan teknik purposive sampling pada kelas VIII yang berjumlah 32 siswa. Instrumen yang digunakan adalah lembar FCE, lembar observasi, penilaian kemampuan gerak siswa dan tes motor educability. Berdasarkan hasil penelitian yang dilakukan dapat disimpulkan bahwa media audio visual menjadi solusi efektif dalam mempelajari dan mengajarkan kemampuan gerak. Pengalaman pandangan dan penyimpanan memori dalam jangka pendek memori dapat digunakan dalam memperbaiki olah gerak yang dikarenakan pengaruh visualisasi yang diterima oleh indera penglihatan dan indera pendengaran. Implikasi dari hasil penelitian ini dapat digunakan rujukan dalam mengajarkan kemampuan gerak yang memerlukan gerakan kombinasi yang kompleks dapat menggunakan media audio visual.